Teaching and Learning Core Values in General Practice/Family Medicine: A Narrative Review - Michels, Nele R. M.; Maagaard, Roar; Švab, Igor; Scherpbier, Nynke (Frontiers in Medicine, 2021)
General Practice/Family Medicine (GP/FM) is a key discipline within primary health care and so by extension for the whole health care system. An essential condition for effective GP/FM care is a work force that is highly qualified. As society is changing rapidly, a revision of the GP/FM definition is ongoing, in addition to a recent movement of identifying related core values. In this paper we want to give an overview on how these new paths and perspectives are currently reflected in GP/FM teaching and training. We selected four core values that fit in with possible future visions: person-centered care, continuity of care, cooperation in care, and community-oriented care. By a narrative review, we observed that GP/FM education towards core values is often built around overarching topics. Teaching and learning take place in specific contexts, most of all through placements within communities, primary care settings or hospital wards. Mixed teaching- and training methods are used combining knowledge, skills and attitude. Furthermore, collaboration with other health professionals and peers is stressed, in addition to the importance of role models, a holistic focus and the involvement of patients. Since these core values are important within GP/FM and rather few studies on the educational aspects and learning tools were found we advocate encouraging each other more to share good practices, certainly the innovative ones specifically related to GP/FM.